Knowledge Accumulation-based Entrepreneurship (KABE) in the Creative Industry: A Case Study of Woodwork Firms in Indonesia - Hadi Kardoyo; Setiowiji Handoyo; Anugerah Yuka Asmara (STI Policy and Management Journal, 2018)
This article describes the activities of knowledge-intensive entrepreneurship (KIE) in four wood craft manufacturers, namely Radio Magno, Stranough Guitar Technologi, Secco Guitar, and Matoa Watch. The four wood craft manufacturers represent KIE activities in the wood craft industry in Indonesia. The products of the four wood craft manufacturers are able to compete and have market share for both domestic and foreign markets. This article shows some lessons from KIE: 1)  Educational background, knowledge, and experience play a significant role in supporting KIE activities, 2) Knowledge base and learning activities support the ability of four creative wood craft manufactures in enhancing innovation and product development, 3) The idea, product concept, and innovation become an important aspect in supporting the ability of the four wood craft manufacturers in the strategy of entering the market and creating market segment for the products, 4) The four creative wood craft manufacturers are able to perform a combination of complementary aspects of KIE (market, technological and institutional opportunities), 5) Ecosystems and cultural aspects are considered as important aspect in supporting the growth of creative industries.